2009
DOI: 10.1515/znc-2009-11-1208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antinociceptive and Anti-Inflammatory Activities of a New Triterpene Saponin from Bauhinia variegata Leaves

Abstract: A new triterpene saponin, named as 23-hydroxy-3α (9), was isolated from the leaves of Bauhinia variegata Linn. In addition, six fl avonoid compounds along with two cinnamic acid derivatives were isolated and identifi ed based on their chromatographic properties, and chemical and spectral data (ESI-high resolution-MS n , 1 H NMR, 13C NMR, 1 H-1 H COSY, HSQC, and HMBC). Compound 9 was found to be nontoxic (LD 50 ) and to have signifi cant anti-infl ammatory and antinociceptive activities. It also showed a slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
8
0
4
Order By: Relevance
“…According to different indigenous medicinal systems of India, the plant is also useful for treatment of skin diseases, wounds, edema, dysentery, ulcers, eye disease, piles, hemorrhoids and snake bite [3][4][5][6][7]. The various biological activities such as antimicrobial, anti-inflammatory, antitumor, cytotoxic and hepatoprotective activities of this plant have also been reported [8][9][10][11][12]. Earlier studies on leaves of B. variegata reported the isolation of insulin like protein, an antiinflammatory triterpenoid saponin and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…According to different indigenous medicinal systems of India, the plant is also useful for treatment of skin diseases, wounds, edema, dysentery, ulcers, eye disease, piles, hemorrhoids and snake bite [3][4][5][6][7]. The various biological activities such as antimicrobial, anti-inflammatory, antitumor, cytotoxic and hepatoprotective activities of this plant have also been reported [8][9][10][11][12]. Earlier studies on leaves of B. variegata reported the isolation of insulin like protein, an antiinflammatory triterpenoid saponin and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…for Bauhenina varigata alcoholic extract, no deaths or toxicity signs and symptoms observed after 24h and 48 h in all concentration that was administered and therefore the LD50 is considered higher than 4000mg/kg (which is the crude or highest extract concentration) and according to (Loomis and Hayes, 1996) its considered slightly toxic. Number of studies reported the LD50 of Buahinia varigata leaves extract after intraperitonial administration experimental animals, (1) and (20) suggested that Bauhenina varigata is safe up to the dose2000mg/kg when administered orally to albino mice, while (21)showed that LD50 for terpens that derived from Bauahenia varigata is 3000mg/kg when administered orally to albino mice. Table (3) showed that the correlation between blood glucose levels for group M1 and M2 and days in compare to the day before starting the treatment is not significant while it's significant for group M3, M4, this is because M1 and M2 didn't receive any treatment during the course of treatment only normal saline 0.09% which has no effect on the blood glucose level, So no changes occurred in the blood glucose level readings.…”
Section: Discussionmentioning
confidence: 99%
“…Active constituent of Bauhinia varigata (bark) promotes conversion of Tyrosine to Thyroxin ,by potentiating the enzyme tyrosinase , Herpestis monnieri stimulate hormone axis (THP) and increases TRF 13,14,15,16,17,18,19 , Hepato stimulant Phyllanthus emblica, Terminalia chebula, Terminalia bellerica promotes active conversion of Cholecalciferol to Calcitrol facilitate optimum calcium concentration to maintain and bioregulate neuro cardiac and muscular activity. In addition immune improving character of Phyllanthus emblica, Active ingradients of Zingiber officinale,Piper longum and Piper nigrum acting as anti inflammatory and stimulant to thyroid pituitary axis promotes thyroid tissue regeneration and bioregulation of thyroid activity .…”
Section: Methodsmentioning
confidence: 99%